Tn10 transposition promotes RecA-dependent induction of a lambda prophage. - Roberts, D (1988)
We present evidence that Tn10 transposition, or a closely correlated event, induces expression of bacterial SOS functions. We have found that lambda prophage induction is increased in Escherichia coli lambda lysogens containing increased Tn10 transposase function plus single or multiple copies of an appropriate pair of transposon ends. This increase occurs by the normal pathway for prophage induction, which involves RecA-mediated cleavage of the phage lambda repressor protein. We also present evidence that Tn10 promotes induction of expression of the E. coli sfiA gene. Tn10 transposes by a nonreplicative mechanism. We propose that the signal for RecA protease activation and SOS induction is generated by degradation of the transposon donor molecule and suggest that SOS induction is biologically important in helping a cell undergoing transposition to repair and/or recover from damage to the transposon donor chromosome.